2021
DOI: 10.1098/rsos.210885
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal fluctuations in musical preference

Abstract: The rhythm of human life is governed by diurnal cycles, as a result of endogenous circadian processes evolved to maximize biological fitness. Even complex aspects of daily life, such as affective states, exhibit systematic diurnal patterns which in turn influence behaviour. As a result, previous research has identified population-level diurnal patterns in affective preference for music. By analysing audio features from over two billion music streaming events on Spotify, we find that the music people listen to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…That said, other approaches in and outside of Twitter have been tested as well, producing complementary and in some cases alternative results. In one instance, online data exploration identified diurnal variations in musical preference on the streaming app, Spotify, where users showed significant preferences for low-valence (more 'sad, depressed') tracks during the night and early morning hours between 11pm and 6am (Heggli et al, 2021). These time trends match the general time trends uncovered for mood among Lumosity and Twitter users, and for suicide posts to Reddit.…”
Section: Discussionmentioning
confidence: 67%
“…That said, other approaches in and outside of Twitter have been tested as well, producing complementary and in some cases alternative results. In one instance, online data exploration identified diurnal variations in musical preference on the streaming app, Spotify, where users showed significant preferences for low-valence (more 'sad, depressed') tracks during the night and early morning hours between 11pm and 6am (Heggli et al, 2021). These time trends match the general time trends uncovered for mood among Lumosity and Twitter users, and for suicide posts to Reddit.…”
Section: Discussionmentioning
confidence: 67%
“…Out of these services, Spotify stands out with over 320 million listeners worldwide in 2020 [ 24 , 25 ]. In addition, Spotify offers an easily accessible API (application programming interface), allowing users and researchers to pull metadata and pre-calculated audio features from millions of unique tracks [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has revealed that such playlists do indeed vary in terms of their Spotify audio features [ 27 ]. Using Spotify data, recent research demonstrated that people’s musical preferences follow a certain pattern depending on the period of the day [ 28 , 29 ]. In other words, Spotify audio features of music that people listen to fluctuate throughout the diurnal cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Spotify audio features of music that people listen to fluctuate throughout the diurnal cycle. Musical preferences are characterized in the morning by high loudness, valence and energy, in the afternoon by an increase in tempo, beat strength and danceability, and during the night by the lowest values of loudness and tempo [ 28 ]. What’s more, a moderately significant correlation between diversity of human activity during the day and variability in the average Spotify audio features has been identified [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation